Central Facial Soft-Tissue Defect Following Surgical Resection: An Algorithm for Reconstruction - Ramadan, Mohamad Rachadian; Atmodiwirjo, Parintosa; Tikyayala, Amila (Lingkar Studi Bedah Plastik Foundation, 2022)
Background: Central facial soft tissue defect poses a unique challenge for the reconstructive surgeon. The three-dimensional properties of the aesthetic facial subunit and its related function are the goals for reconstruction. Considering the prominent social role of the face, the procedure to achieve a good quality of life for patients may cost more than a single surgery. This single-center study presents an algorithm of treatment for central facial soft tissue defect and it’s proposed classification according to the authors’ experiences. Methods: A retrospective review of medical records and photos of patients who underwent central facial soft tissue defect reconstruction in Cipto Mangunkusumo National Hospital, Jakarta, Indonesia, from 2009 to 2019. Patients who underwent free flap reconstruction were followed up, and the primary outcomes were assessed using the FACE-Q head and neck cancer (FACE-Q H&N) scale. A classification system for central facial soft tissue defect with seven subtypes (1–7) based on the facial subunit and its treatment was proposed. Results: Twenty-five patients were included. The malignant tumor was the main etiology (88%), with basal cell carcinoma being the primary cancer pathology (64%). The average defect size was 120 cm2 (32-416 cm2) and most defects fell into subtype 6 of the classification (32%). Anterolateral thigh free flap (ALT) was the main flap of choice (64%), followed by radial forearm free flap (36%), with 92% of flaps succeeding rate from this series. All of the patients underwent at least one ancillary procedure following the reconstruction, while the average was 2 (1-6) procedures. FACE-Q H&N outcomes, especially on the appearance and appearance distress scale, showed a low to moderate score with a 72% response rate. Conclusions: Central facial soft-tissue defect continues to challenge reconstructive surgeons. While the advances in free tissue transfer might improve the general outcomes, the numerous and costly secondary procedures do not usually end up in the best appearance. This study displayed the need for modern reconstruction modalities that provide high satisfaction in aesthetic and functional outcomes with fewer secondary procedures. Vascularized Composite Allotransplantation (VCAT) might be the future choice.